Why it pays for aid recipients to take note of the millennium challenge corporation: Other donors do! - Axel Dreher; Peter Nunnenkamp; Hannes Öhler (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2010)
It is widely believed that the Millennium Challenge Corporation (MCC) has grossly fallen short of high expectations raised by the Bush administration in 2002. From the perspective of potential recipient countries, the crucial issue is whether the MCC increased the overall pool of aid resources available to them. We argue that this question extends far beyond the distribution of the limited MCC resources. By employing OLS and treatmenteffects estimations, we assess how other US aid agencies and non-US donors reacted to MCC decisions. We find that positive signaling effects tend to dominate possible substitution effects not only for overall US aid but also for multilateral donors. Regarding other bilateral donors the evidence is mixed.
Keywords: F35; 330; official development aid; Millennium Challenge Corporation; additionality; signaling; United States; other DAC donors; Entwicklungshilfe; Amerikanisch; Wirkungsanalyse; Entwicklungskooperation; Signalling; USA; Welt; Entwicklungsländer